Physical activity a multi-disciplinary introduction - Draper, Nick (Nicholas); Stratton, Gareth 1960- (Routledge, 2019)
Physical activity and its relationship to health is one of the great issues of our age. The cause of, and solution to, physical inactivity are complex and multi-dimensional, and therefore the subject needs to be studied and understood from a variety of perspectives. this is the first textbook to provide a truly multi-disciplinary introduction to physical activity studies. Offering a complete foundation to the subject, it covers the basics of every core discipline, from biochemistry, public health and biomechanics to physiology, sport psychology and sociology. It introduces a full range of topics across the physical activity curriculum, including behaviour change, motor skills development, nutrition, exercise prescription, public health policy, and physical education, providing a well-balanced and international perspective on each important issue. There is also a strong emphasis throughout the book on the practical, applied dimensions of physical activity, including innovative approaches to promotion and intervention tailored to every age range and environment.